Setting the global research agenda for community health systems: literature and consultative review - Smisha Agarwal; Karen Kirk; Pooja Sripad; Ben Bellows; Timothy Abuya; Charlotte Warren (BMC, 2019)
Abstract Background Globally, there is renewed interest in and momentum for strengthening community health systems, as also emphasized by the recent Astana Declaration. Recent reviews have identified factors critical to successful community health worker (CHW) programs but pointed to significant evidence gaps. This review aims to propose a global research agenda to strengthen CHW programs. Methods and results We conducted a search for extant systematic reviews on any intermediate factors affecting the effectiveness of CHW programs in February 2018. A total of 30 articles published after year 2000 were included. Data on research gaps were abstracted and summarized under headings based on predominant themes identified in the literature. Following this data gathering phase, two technical advisory groups comprised of experts in the field of community health-including policymakers, implementors, researchers, advocates and donors-were convened to discuss, validate, and prioritize the research gaps identified. Research gap areas that were identified in the literature and validated through expert consultation include selection and training of CHWs, community embeddedness, institutionalization of CHW programs (referrals, supervision, and supply chain), CHW needs including incentives and remuneration, governance and sustainability of CHW programs, performance and quality of care, and cost-effectiveness of CHW programs. Priority research questions included queries on effective policy, financing, governance, supervision and monitoring systems for CHWs and community health systems, implementation questions around the role of digital technologies, CHW preferences, and drivers of CHW motivation and retention over time. Conclusions As international interest and investment in CHW programs and community health systems continue to grow, it becomes critical not only to analyze the evidence that exists, but also to clearly define research questions and collect additional evidence to ensure that CHW programs are effective, efficient, equity promoting, and evidence based. Generally, the literature places a strong emphasis on the need for higher quality, more robust research.